Association between emergency department disposition and mortality in patients with COVID‐19 acute respiratory distress syndrome - Lebold, Katie M.; Moore, Andrew R.; Sanchez, Pablo A.; Pacheco‐Navarro, Ana E.; O'Donnell, Christian; Roque, Jonasel; Parmer, Caitlin; Pienkos, Shaun; Levitt, Joseph; Collins, William J.; Rogers, Angela J.; Wilson, Jennifer G. (Journal of the American College of Emergency Physicians Open, 2024)
Patients hospitalized for COVID‐19 frequently develop hypoxemia and acute respiratory distress syndrome (ARDS) after admission. In non‐COVID‐19 ARDS studies, admission to hospital wards with subsequent transfer to intensive care unit (ICU) is associated with worse outcomes. We hypothesized that initial admission to the ward may affect outcomes in patient with COVID‐19 ARDS. This was a retrospective study of consecutive adults admitted for COVID‐19 ARDS between March 2020 and March 2021 at Stanford Health Care. Mortality scores at hospital admission (Coronavirus Clinical Characterization Consortium Mortality Score [4C score]) and ICU admission (Simplified Acute Physiology Score III [SAPS‐III]) were calculated, as well as ROX index for patients on high flow nasal oxygen. Patients were classified by emergency department (ED) disposition (ward‐first vs. ICU‐direct), and 28‐ and 60‐day mortality and highest level of respiratory support within 1 day of ICU admission were compared. A second cohort (April 2021‒July 2022, n = 129) was phenotyped to validate mortality outcome. A total of 157 patients were included, 48% of whom were first admitted to the ward (n = 75). Ward‐first patients had more comorbidities, including lung disease. Ward‐first patients had lower 4C and similar SAPS‐III score, yet increased mortality at 28 days (32% vs. 17%, hazard ratio [HR] 2.0, 95% confidence interval [95% CI] 1.0‒3.7, p = 0.039) and 60 days (39% vs. 23%, HR 1.83, 95% CI 1.04‒3.22, p = 0.037) compared to ICU‐direct patients. More ward‐first patients escalated to mechanical ventilation on day 1 of ICU admission (36% vs. 14%, p = 0.002) despite similar ROX index. Ward‐first patients who upgraded to ICU within 48 h of ED presentation had the highest mortality. Mortality findings were replicated in a sensitivity analysis. Despite similar baseline risk scores, ward‐first patients with COVID‐19 ARDS had increased mortality and escalation to mechanical ventilation compared to ICU‐direct patients. Ward‐first patients requiring ICU upgrade within 48 h were at highest risk, highlighting a need for improved identification of this group at ED admission.